2018
DOI: 10.3329/jbsp.v12i2.35422
|View full text |Cite
|
Sign up to set email alerts
|

Serum amylase and lipase levels in type 2 diabetes mellitus

Abstract: Background: In diabetes mellitus, impaired pancreatic endocrine activity may affect its exocrine function causing mal digestion and malnutrition.Objective: To assess serum amylase and lipase levels in subjects with type 2 diabetes mellitus (T2DM).Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from January 2015 to December 2015. Fifty type 2 diabetic subjects with age ranging from 40 to 55 years of both sexes were enrolled in this study and 50 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
(14 reference statements)
2
10
0
Order By: Relevance
“…Previous reports published alteration of serum pancreatic amylase and lipase enzymes in patients with T1DM and T2DM. 15 , 16 In our experiment, the serum levels of amylase and lipase in the treated groups dramatically modulated compared to the diabetic control group, which is in agreement with the previous studies. In summary, it seems that Actinomycetales species can have an improvement effect for attenuation of side effects in various diabetes complications.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports published alteration of serum pancreatic amylase and lipase enzymes in patients with T1DM and T2DM. 15 , 16 In our experiment, the serum levels of amylase and lipase in the treated groups dramatically modulated compared to the diabetic control group, which is in agreement with the previous studies. In summary, it seems that Actinomycetales species can have an improvement effect for attenuation of side effects in various diabetes complications.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, lipase enzymes catalyse the hydrolysis of ester bonds of triglycerides, and elevated serum lipase activity is implicated in t2ds [ 45 ]. Using the ligand fishing technique, isovitexin was identified as a lipase enzyme inhibitor [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Study reported that dietary fibre deficiency led to insulin‐resistant in humans (Jenkins et al., 2000). In the insulin‐resistant state, the pancreas exocrine acinar cells emerged atrophy and serum lipase levels decreased in humans (Tanvi et al., 2017). However, this mechanism is only our speculation and it needs further investigation.…”
Section: Discussionmentioning
confidence: 99%